Spectrophotometric determination of Procaine penicillin in pure and pharmaceutical formulations using metol (Baghdad Science Journal, 2008)
A simple, accurate and sensitive spectrophotometric method for the determination of Procaine penicillin (PP) is described. The method is based on charge-transfer reaction of PP with metol (N-methyl-p-hydroxy aniline) in the presence of ferric sulphate to form a purple-water soluble complex ,which is stable and has a maximum absorption at 510 nm .A graph of absorbance versus concentration shows that Beer’s low is obeyed over the concentration range of 3-80 µg /ml of PP (i.e.,3-80 ppm) with a molar absorbativity of 4.945 ×103 L.mol-1.cm-1 ,Sandell sensitivity of 0.1190 µg cm-2 ,a relative error of (-1.57)-2.79 % and a standard deviation of less than 0.59 depending on the concentration of PP.The optimum conditions for full colour development are described and the proposed method was probably applied satisfactorily to pharmaceutical injections containing PP.